(untitled) (Al-Qamar, 2021)
This article is a critical study of Prof. Muhammad Munawar`s translated version of “Al-Fitna-tul-Kubra, Usmān”, by Dr. Taha Hossian an Egyptian man of letters. This book highlights the sensitive issues of Islamic history related to the martyrdom of Hazrat Usmān (RA). Prof. Muhammad Munawwar is inclined to faithful translation instead of idiomatic one which hampers not only the lucidity and rhythm but also the comprehension of the contents . Since the translator is a genuine writer and critic, the translation generally reflects the literary flavour. The sensitivity of the contents of the book demands a careful selection of words not only on the part of Dr. Taha Hossain but also the translator, Prof. Muhammad Munawwar. However, both of them laboured in terms of the use of diction to do justice with the sensitivity and criticality of the topic.